A Philosophical Study of the Transformation of Islamic Education Policy Based on Local Wisdom in West Sumatra: Irwan Prayitno's Leadership Perspective - Firnanda, Rizky; Adnan, Irfan Maulana; Jannah, Lutpita Firdatul; Azizah, Afifah Nur; Faradhila, Ninda; Alfareza, M. Rizki (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
Education plays an important role not only in transmitting knowledge but also in shaping students’ moral, cultural, and religious character. In West Sumatra, the transformation of Islamic education policy during Irwan Prayitno’s leadership was closely linked to local wisdom rooted in the Minangkabau philosophy of adat basandi syara’, syara’ basandi Kitabullah (ABS-SBK). This study aims to analyze the philosophical foundation and policy transformation of local wisdom-based Islamic education in West Sumatra under his leadership. This research employed a descriptive qualitative approach enriched with philosophical analysis. Data were obtained through a semi-structured interview with Irwan Prayitno as the key informant, supported by documentation and relevant literature. The findings show that local wisdom was understood not merely as cultural symbolism, but as a value system grounded in Islamic teachings and reflected in educational orientation, Qur’anic learning programs, khatam Al-Qur’an, mentoring activities, and the inclusion of Budaya Alam Minangkabau (BAM). The study also finds that the implementation of these policies faced several challenges, particularly the limited number of teachers with sufficient knowledge of customary values and the lack of practical teaching materials. In addition, the findings indicate that local wisdom-based education contributed more clearly to character formation than to measurable educational quality, since the latter requires more systematic indicators. Theoretically, this study contributes to the discourse on Islamic education, local wisdom, and leadership by showing how educational policy transformation can be understood through the interconnection of culture, religion, and regional leadership. Practically, this study highlights the importance of strengthening teacher capacity and improving culturally grounded learning materials to support the implementation of local wisdom-based education in West Sumatra.